SIA's Contribution to Interdisciplinary Projects in Engineering. (2015) - Ogrezeanu, Andreea
Abstract: Interdisciplinary developments in engineering create challenges with regards to how resulting projects, technologies, activities impact their broader environment. Under the paradigm of sustainable development, concerns with maximizing positive impacts and minimizing negative impacts are raised. Social impact assessment has been developed in the context of large industrial projects. For the past about forty years a complex theoretical and practical ground has been developed, sustained by regulations that enforce the use of SIA. Under the sustainable development paradigm, SIA is regarded as a process of analysis that aims to anticipate and manage any intended and unintended impacts generated by planned interventions within the human (and natural environment). As a result SIA becomes a valuable contributor for data-based decision making within management processes. The most recent distinctions with regards to SIA are aiming to position this tool rather ex-ante than ex-post within a planned intervention (project, investment, policy, etc.)[10] . This paper explores into pathways to use SIA tools within engineering projects and emphasize the contributions brought about by the use of such tools.